Biocomposite Materials and Its Applications in Acoustical Comfort and Noise Control - Md, Rezaur Rahman; Sinin, Hamdan; Jayamani, Elammaran; Muhammad Khusairy, Bin Bakri; Md. Saiful, Islam (Springer International Publishing, 2017)
In this chapter, an overview of various composite materials for sound absorption applications were reported and discussed in details. This includes composites made of polymer matrix reinforced with synthetic fibers and with natural fibers. This chapter also deals with composites made of recycled materials, bio-based matrix and bio-based fiber materials, hybrid biodegradable materials and surface treatment fiber composites for sound absorption applications. New developments dealing with composite materials made of lignocellulosic fiber and the pros and cons of synthetic fibers and natural fibers were also studied. This chapter also examines the critical issues regarding on composite materials and the scientific challenges faces by researchers and industries that require further research and development of composite materials made from polymer composites for their increased acceptance in the modern world for sound absorption purpose.